A method for preparing a nitride ceramic phase reaction precipitation strengthened high entropy alloy

By using urea-induced in situ nitride ceramic phase precipitation in CoCrFeMnNi high-entropy alloys, combined with rapid hot pressing sintering technology, the trade-off between strength and ductility of high-entropy alloys is solved, and the strengthening effect of high strength and excellent plastic toughness is achieved.

CN118880091BActive Publication Date: 2025-03-07SOUTHWEST JIAOTONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410941694.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-15
Publication Date
2025-03-07
Estimated Expiration
2044-07-15

AI Technical Summary

Technical Problem

Single-phase high-entropy alloys have tradeoffs between strength and ductility. For example, CoCrFeMnNi high-entropy alloys exhibit high ductility but low strength, limiting their application in complex operating conditions.

Method used

Using rapid hot press sintering technology, urea is added to CoCrFeMnNi high-entropy alloy, and the ammonia released from urea at high temperature is used as the nitrogen source to precipitate the nitride ceramic phase in situ to strengthen the high-entropy alloy.

Benefits of technology

By precipitating nitride ceramic phases in situ, the strength and plastic toughness of high-entropy alloys are significantly improved, and the problem of weak interfacial bonding ability between alloys and ceramic phases in traditional methods is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118880091B_ABST
    Figure CN118880091B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of alloy preparation, and specifically discloses a method for preparing a nitride ceramic phase reaction precipitation strengthening high entropy alloy, which is specifically: urea and CoCrFeMnNi high entropy alloy powders of a certain mass ratio are ball-milled and mixed, and a nitride ceramic phase is precipitated by in-situ reaction by rapid hot pressing sintering, and Ar is introduced as a protective gas during the sintering process, and a nitride ceramic phase reaction precipitation strengthening high entropy alloy is obtained after hot pressing sintering. The nitride ceramic phase reaction precipitation strengthening high entropy alloy prepared by the present invention significantly improves the strength of the CoCrFeMnNi high entropy alloy and retains a relatively high plasticity, thereby improving the application potential of the alloy as a high-performance structural material under various complex working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy preparation, and specifically discloses a method for preparing a nitride ceramic phase reaction precipitation strengthened high entropy alloy. Background Art

[0002] In recent years, high entropy alloys have attracted much attention for their unique comprehensive properties. High entropy alloys refer to alloys composed of five or more elements, with the atomic percentage of each element ranging from 5% to 35%. Compared with traditional alloys, high entropy alloys exhibit significant characteristics, including high entropy effect in thermodynamics, lattice distortion effect in structure, slow diffusion effect in kinetics, and "cocktail" effect in performance. These excellent properties make high entropy alloys the focus of research and development of high-performance structural materials in the future. In general, strength and ductility are two basic properties of structural materials. However, previous studies have observed that there is a trade-off between strength and ductility in single-phase high entropy alloys. For example, the single-phase face-centered cubic (FCC) CoCrFeMnNi high entropy alloy exhibits high ductility but low strength, which greatly limits the application of this alloy as a structural material under various complex working conditions. Summary of the invention

[0003] In order to solve the above problems, the present invention discloses a method for preparing a nitride ceramic phase in-situ reaction precipitation strengthened high entropy alloy, wherein the CoCrFeMnNi high entropy alloy is prepared by rapid hot pressing and sintering, and in order to further improve the strength of the CoCrFeMnNi high entropy alloy, urea is added to the high entropy alloy powder, and ammonia released by urea at high temperature is used as a nitrogen source to in-situ precipitate a nitride ceramic phase in the CoCrFeMnNi high entropy alloy, thereby obtaining a nitride ceramic phase strengthened CoCrFeMnNi high entropy alloy.

[0004] The present invention includes the following technical solutions:

[0005] A method for preparing a nitride ceramic phase reaction precipitation strengthened high entropy alloy comprises the following steps:

[0006] Step 1: Raw material preparation: CoCrFeMnNi high entropy alloy powder and urea powder with a purity of ≥99.9%.

[0007] Step 2: Ball milling mixing: Pour the mixed powder of CoCrFeMnNi high entropy alloy powder and urea in different mass ratios into a vacuum stainless steel grinding tank equipped with stainless steel grinding balls, then put it into a planetary ball mill for ball milling, pour the blended powder into a metal plate, sieve it and put it into a vacuum drying oven for standby use.

[0008] Step 3: In-situ reaction to precipitate nitride ceramic phase: Place the mixed powder of CoCrFeMnNi high entropy alloy powder and urea into a graphite mold, remove the air in the furnace and introduce inert gas, sinter at high temperature and keep warm for a period of time.

[0009] Step 4: Rapid hot pressing sintering: The pre-sintered alloy after reaction hot pressing sintering is further sintered to form and densify, sintered at high temperature and kept warm for a period of time, and cooled with the furnace to obtain a high entropy alloy.

[0010] Furthermore, in step 1, the particle size range of the CoCrFeMnNi high entropy alloy powder can be 1-53 μm, and the urea is solid crystalline particles.

[0011] Furthermore, in step 2, the amount of urea added is 1-7 wt. % by weight.

[0012] Furthermore, in step 2, the rotation speed of the ball mill can be 150-300 rpm, and the time can be 1-10 h.

[0013] Furthermore, in step 3, the vacuum is evacuated to below 10 Pa, and the inert gas is used for washing three times until the furnace is filled with the inert gas.

[0014] Preferably, the inert gas in step 3 is high-purity argon.

[0015] Furthermore, in step 3, the heating rate is 100°C / min, from room temperature to 500-700°C, the pressure is 5MPa, and the temperature is kept for 60min; during this period, urea is completely volatilized to generate ammonia (the urea decomposition process is as shown in Formula 1 below), which reacts with the strong nitriding element Cr in the CoCrFeMnNi high entropy alloy to precipitate the Cr2N ceramic strengthening phase in situ. At the same time, high-purity argon is introduced to provide a slight positive pressure to prevent the ammonia from being removed too quickly.

[0016]

[0017] Furthermore, in step 4, the temperature is increased from 500-700°C to 900-1100°C at a heating rate of 50°C / min; the pressure is increased from 5MPa to 50MPa, and the holding time is 10min. The entire sintering process is carried out under vacuum (less than 10Pa).

[0018] Furthermore, the present invention discloses a strengthened high entropy alloy obtained by any of the preparation methods described above.

[0019] Compared with the prior art, the present invention has the following outstanding beneficial effects:

[0020] The present invention provides a nitride ceramic phase in-situ reaction precipitation strengthening high entropy alloy, which uses rapid hot pressing sintering technology to shorten the heat preservation time and prevent grain growth; on the other hand, it ensures that the nitride ceramic strengthening phase is precipitated in-situ inside the high entropy alloy, effectively avoiding the problem of weak interface bonding ability between the alloy and the ceramic phase caused by the traditional method of mixing alloy powder and ceramic powder before sintering. The in-situ precipitation of the ceramic phase inhibits the growth of high entropy alloy grains, achieving the purpose of fine grain strengthening and second phase precipitation strengthening. Compared with the prior art, the raw materials of this method are easy to obtain, the preparation process is simple, and it has better plasticity and toughness while improving the strength of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram of the rapid reaction hot pressing sintering principle of the present invention.

[0022] Figure 2 This is the heating and cooling curve of the high entropy alloy sintering of the present invention.

[0023] Figure 3 XRD spectra of the nitride-reinforced high entropy alloys of Examples 1-4 of the present invention and Comparative Example 1.

[0024] Figure 4 This is a backscattered electron morphology image of the nitride-strengthened high entropy alloy prepared in Examples 1-4 of the present invention.

[0025] Figure 5 This is a Vickers hardness diagram of the nitride-reinforced high entropy alloys prepared in Examples 1-4 of the present invention and Comparative Example 1.

[0026] Figure 6 Room temperature compressive stress-strain curves and room temperature tensile stress-strain curves of the nitride-strengthened high entropy alloys prepared in Examples 1-4 of the present invention and Comparative Example 1.

[0027] Figure 7 The IPF diagram and phase distribution diagram of the EBSD of the nitride ceramic phase reaction precipitation strengthened high entropy alloy prepared in Example 3 and Examples 5-6 are shown.

[0028] Figure 8 Room temperature compressive stress-strain curves and room temperature tensile stress-strain curves of the nitride-strengthened high entropy alloys prepared in Example 3 and Examples 5-6 of the present invention. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] CoCrFeMnNi high entropy alloy powder (Nanjing Mingchang New Materials Co., Ltd.)

[0031] Urea powder (Shanghai Aladdin Biochemical Technology Co., Ltd.)

[0032] Example 1

[0033] Step 1: Raw material preparation: CoCrFeMnNi high entropy alloy spherical powder (particle size 15-53 μm, purity ≥99.9%); urea powder (purity >99.5%).

[0034] Step 2: Ball milling mixture: Pour a mixed powder of CoCrFeMnNi high entropy alloy powder and urea in a certain mass ratio into a vacuum stainless steel grinding jar equipped with stainless steel grinding balls (mass ratio CoCrFeMnNi high entropy alloy powder: urea powder = 99:1), and then put it into a planetary ball mill for ball milling (the speed of the ball mill is 180 rpm, and the time is 2 h), pour the blended powder into a metal plate, sieve it, and put it into a vacuum drying oven for use.

[0035] Step 3: In-situ reaction to precipitate nitride ceramic phase: The principle is as follows Figure 1 As shown, the mixed powder of CoCrFeMnNi high entropy alloy powder and urea is poured into a high-purity graphite mold with a diameter of Φ40mm (Hebei Jingtan Technology Co., Ltd.), and the vacuum is evacuated to below 10Pa, and the inert gas high-purity argon is used to wash three times until it is full of inert gas. During the final washing, high-purity argon is kept in the furnace, and a slightly positive pressure is maintained. The temperature is raised from room temperature to 565℃ at a rate of 100℃ / min, the pressure is 5MPa, and the temperature is kept for 60min; during this period, urea is completely volatilized to generate ammonia, which reacts with the strong nitriding element Cr in the CoCrFeMnNi high entropy alloy to precipitate the Cr2N ceramic strengthening phase in situ.

[0036] Step 4: Vacuum rapid hot pressing sintering: The heating and cooling curves are as follows: Figure 2 As shown, the vacuum degree in the furnace is evacuated to less than 10Pa for vacuum rapid hot pressing sintering, and the temperature is raised from 565℃ to 1000℃ at a heating rate of 50℃ / min; the heat preservation time is 10min, and finally the furnace is cooled to obtain a ceramic phase strengthened high entropy alloy.

[0037] Embodiment 2-4

[0038] The preparation method is the same as in Example 1, except that the doping amount of urea is changed. The specific parameters are shown in Table 1.

[0039] Table 1 Addition amount of main components in Examples 2-4

[0040]

[0041] Example 5

[0042] Step 1: Same as Example 1.

[0043] Step 2: Ball milling mixing: Weigh a certain mass ratio of high entropy alloy powder and urea powder (CoCrFeMnNi high entropy alloy powder mass: urea powder mass = 95wt.%: 5wt.%) respectively, adopt a wet milling blending process, first dissolve 5wt.% of urea in 5ml of deionized water, and then place the urea solution and CoCrFeMnNi high entropy alloy powder in a vacuum stainless steel grinding tank equipped with stainless steel grinding balls for ball milling (the speed of the ball mill is 180rpm, and the time is 2h), then take out the powder and remove water by freeze drying, sieve it and put it into a vacuum drying oven for use.

[0044] Step 3: Same as Example 1.

[0045] Step 4: Same as Example 1.

[0046] Example 6

[0047] Step 1: Raw material preparation: CoCrFeMnNi high entropy alloy spherical powder (particle size <15 μm, purity ≥99.9%); urea powder (purity >99.5%).

[0048] Step 2: Same as Example 5.

[0049] Step 3: Same as Example 1.

[0050] Step 4: Same as Example 1.

[0051] Table 2 Comparison of blending methods and powder particle sizes in Examples 5-6 and Example 3

[0052]

[0053] Comparative Example 1

[0054] Step 1: Raw material preparation: CoCrFeMnNi high entropy alloy spherical powder with a particle size range of 15-53 μm and a purity of ≥99.9%.

[0055] Step 2: Vacuum rapid hot pressing sintering: Pour the ball-milled high-entropy alloy powder into a high-purity graphite mold with a diameter of Φ40mm, and heat it up at a rate of 100℃ / min and a pressure of 5MPa below 715℃; then, in 1 minute, the temperature rises from 715℃ to 750℃, the pressure rises from 5MPa to 50MPa, and then rises to 800℃, 900℃, 1000℃, and 1100℃ at a rate of 50℃ / min (the four groups of samples are named G800, G900, G1000, and G1100, respectively); the holding time is 10 minutes, and the entire sintering process is carried out under vacuum (less than 10Pa), and the sintering is completed and cooled with the furnace. A high-entropy alloy is obtained.

[0056] The nitride ceramic phase reaction precipitation strengthened high entropy alloys prepared in Examples 1 to 6 and the high entropy alloy prepared in Comparative Example 1 were tested respectively:

[0057] Depend on Figure 3 It can be seen that the phase structures of the nitride ceramic phase reaction precipitation strengthened high entropy alloys prepared in Examples 1-4 and the high entropy alloy prepared in Comparative Example 1 were analyzed by XRD. All high entropy alloys showed FCC phase structure, and the (111) crystal plane diffraction peak of Cr2N appeared in the XRD spectrum of the CoCrFeMnNi high entropy alloy sample after adding urea. The backscattered electron imaging images of the CoCrFeMnNi high entropy alloys with different urea addition amounts prepared in Examples 1-4 are shown in the attached figure. Figure 4 As shown in the figure, according to the principle of backscattered electron imaging, the marking of the area where the phase Cr2N is located is shown in the figure. The figure shows that there are two main forms of Cr2N particles inside the high entropy alloy matrix. The first is that the fine particles in the high entropy alloy matrix are dispersed, and with the increase of urea addition, the number of dispersed Cr2N particles also increases.

[0058] Attached Figure 5 The Vickers hardness of different high entropy alloys is shown in the figure: 187HV, 217HV, 229HV, 260HV and 270HV, indicating that the hardness of the high entropy alloy is improved with the doping of urea. Figure 6 The compressive engineering stress-strain curves and tensile engineering stress-strain curves of different CoCrFeMnNi high entropy alloys obtained through compression tests and tensile tests are shown in the figure.

[0059] Figure 6 (a) It can be found that all samples showed extremely high plasticity, and no fracture occurred when the compressive strain reached 50%. The compressive yield strengths of the five groups of samples were 365MPa, 495MPa, 543MPa, 645MPa and 660MPa, respectively. The sample with 7% urea addition showed the highest compressive yield strength, and its compressive yield strength was increased by 81% compared with the CoCrFeMnNi high entropy alloy without urea addition.

[0060] In order to further study the effect of urea addition on the plasticity of CoCrFeMnNi high entropy alloy, tensile tests were carried out on five groups of samples. Figure 6 (b) It can be found that the ultimate tensile strength of the five groups of samples are 684MPa, 845MPa, 908MPa, 925MPa and 940MPa, respectively, and their elongations are 58%, 44%, 41%, 29% and 19%, respectively. It can be found that with the addition of urea, the tensile and compressive strengths of the CoCrFeMnNi high entropy alloy are significantly improved, while the plasticity decreases with the increase of urea content. Among them, the sample with 5% urea addition showed the best mechanical properties, and the tensile strength was increased by about 35% compared with the CoCrFeMnNi high entropy alloy without urea addition. In terms of plasticity, the elongation of nearly 30% is still retained.

[0061] Figure 7 The IPF map and phase distribution map of the nitride ceramic phase reaction precipitation strengthening high entropy alloy EBSD prepared in Example 3 and Example 5-6 are shown. For the 5% sample prepared by dry grinding and blending, its phase distribution map shows that the distribution of the Cr2N precipitation phase is not uniform, and it is mainly enriched in the small-sized grains inside the sample. This shows that during the sintering process, due to the enrichment of urea, the nitridation of small-sized alloy particles is more sufficient, resulting in the enrichment of the Cr2N precipitation phase in small-sized grains. For the 5% coarse W sample prepared by wet grinding and blending, the phase distribution map shows that the Cr2N precipitation phase is uniformly distributed in the high entropy alloy matrix. This is because through the wet grinding and blending method, urea and alloy powder have been uniformly mixed before sintering, and urea is distributed around alloy particles of different particle sizes. During the sintering process, urea can provide a uniform nitrogen source concentration, so that the Cr2N ceramic phase can be precipitated in situ around almost every high entropy alloy particle. At the same time, it can be observed from the figure that there are relatively few Cr2N ceramic phases at the grain boundaries of high entropy alloys with larger grain sizes. This is due to the large particle size of the alloy particles, which makes it impossible for the internal part to fully contact the nitrogen source. The third group of 5% fine W samples was prepared by wet grinding and blending with alloy powders with finer particle sizes. Compared with the second group of 5% coarse W samples, the main difference is that the grain size of the matrix phase of the obtained high entropy alloy samples is finer, and the distribution of the Cr2N ceramic phase is more uniform and the density is higher.

[0062] In summary, by adopting the wet grinding blending method, the Cr2N precipitate phase can be evenly distributed in the high entropy alloy matrix, and the problem of Cr2N precipitate phase enrichment at small grain sizes inside the alloy is solved. By using alloy powder with a smaller particle size, a more evenly distributed Cr2N ceramic precipitate phase can be obtained under the same urea addition amount.

[0063] Figure 8The compressive engineering stress-strain curves and tensile engineering stress-strain curves of the nitride ceramic phase reaction precipitation strengthened high entropy alloys prepared in Example 3 and Example 5-6 at room temperature are shown. Figure 8 (a) It can be observed that all samples show extremely high plasticity, and no fracture occurs when the compressive strain reaches 40%. The compressive yield strengths of the three groups of samples are 645MPa, 703MPa and 838MPa respectively. Among them, the 5% fine W sample shows the highest compressive yield strength. Figure 8 (b) shows that the ultimate tensile strength of the three groups of samples are 925MPa, 950MPa and 995MPa, and the elongation is 29%, 30% and 26%, respectively. The 5% coarse W sample has a slight improvement in strength and plasticity compared to the 5% sample, while the 5% fine W sample with finer grains shows the highest tensile strength of 995MPa. The above mechanical properties results show that the use of wet grinding blending and alloy powder with smaller particle size can make the Cr2N precipitate phase precipitate more uniformly inside the alloy, thereby improving the distribution uniformity of the precipitate phase and further improving the strength of the CoCrFeMnNi high entropy alloy.

[0064] It can be seen from the above embodiments and comparative examples that the present invention introduces nitrogen into the CoCrFeMnNi high entropy alloy system through a rapid hot pressing sintering process, so that the nitrogen reacts with the strong nitriding metal element Cr in the alloy, and precipitates a Cr2N nitride ceramic phase in situ, thereby improving the mechanical properties of the CoCrFeMnNi high entropy alloy, achieving the effect of strong and tough integration, and improving the application potential of the alloy as a structural material under various complex working conditions.

[0065] The above are only a few preferred embodiments of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a nitride ceramic phase reaction precipitation strengthened high entropy alloy, characterized in that: The following steps are involved: Step 1: Raw material preparation: CoCrFeMnNi high entropy alloy powder and urea powder with a purity of ≥99.9%; The particle size of the CoCrFeMnNi high entropy alloy powder is 1-53 μm, and the urea is solid crystalline particles; Step 2: Ball milling: Pour the mixed powder of CoCrFeMnNi high entropy alloy powder and urea into a vacuum stainless steel grinding tank equipped with stainless steel grinding balls, then put it into a planetary ball mill for ball milling, pour the mixed powder into a metal plate, sieve it and put it into a vacuum drying oven for standby use; The amount of urea added is 1-7wt.% of the total mass of the mixed powder; Step 3: In-situ reaction to precipitate nitride ceramic phase: the mixed powder of the CoCrFeMnNi high entropy alloy powder obtained in step 2 and urea is placed in a graphite mold, the air in the furnace is evacuated and an inert gas is introduced, and the mixture is sintered at a high temperature and kept warm for a period of time to obtain a pre-sintered alloy; Step 4: Rapid hot pressing sintering: The pre-sintered alloy obtained in step 3 is further sintered to form and densify, sintered at high temperature and kept warm for a period of time, and cooled with the furnace to obtain a reinforced high entropy alloy.

2. The method for preparing a nitride ceramic phase reaction precipitation strengthened high entropy alloy according to claim 1, characterized in that: In step 2, the rotation speed of the ball mill is 150-300 rpm, and the time is 1-10 h.

3. The method for preparing a nitride ceramic phase reaction precipitation strengthened high entropy alloy according to claim 1, characterized in that: In step 3, the vacuum is evacuated to below 10 Pa, and an inert gas is used for purging three times until the furnace is filled with the inert gas.

4. The method for preparing a nitride ceramic phase reaction precipitation strengthened high entropy alloy according to claim 1, characterized in that: In step 3, the heating rate is 100°C / min, from room temperature to 500-700°C, the pressure is 5MPa, and the temperature is kept for 60min; during this period, urea is completely volatilized to generate ammonia, which reacts with the strong nitriding element Cr in the CoCrFeMnNi high entropy alloy to precipitate a Cr2N ceramic strengthening phase in situ, and high-purity argon is introduced at the same time to provide a slight positive pressure to prevent the ammonia from being discharged too quickly.

5. The method for preparing a nitride ceramic phase reaction precipitation strengthened high entropy alloy according to claim 1, characterized in that: In step 4, the heating rate is 50°C / min, the temperature rises from 500-700°C to 900-1100°C; the pressure rises from 5MPa to 50MPa, the insulation time is 10min, and the entire sintering process is carried out under a vacuum degree of less than 10Pa.

6. A reinforced high entropy alloy, characterized in that: Obtained by the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • High-entropy alloy and method for preparing high-entropy alloy block through powder metallurgy method

    CN107829007A